Comunicação, mito e sincronicidade: um olhar sobre a obra de Mircea Eliade - Klautau, Carolina Moura (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
This is a comprehensive gaze upon mythologist Mircea Eliade’s works The myth of the eternal return and The sacred and the profane. Mythical narratives originated in different cultures are more connected by meaning than by cause and effect logics. Thus, in this paper we understand myth and communication as two ways of guidance in the world, also adding Carl Gustav Jung’s and Wolfgang Pauli’s notion of synchronicity as a possible key for connections between myths. In the comprehension as a method’s process of “weaving together”, we establish dialogues with different forms of knowledge in our route – myth, communication, psychiatry and modern physics. Cremilda Medina, Joseph Campbell and Dimas Künsch lend us their perceptions in this work.